Study of influence of Catha edulis (Khat) chewing on oral pharmacokinetics of irbesartan in rats using a newly developed HPLC-UV method - Hassan A. Alhazmi; Mustafa A. Bakri; Yahya A. Mohzari; Yousef G. Alshigaify; Mohammed Al Bratty; Sadique A. Javed; Asim Najmi; Ziaur Rehman; Waquar Ahsan; Manal Mohamed Elhassan Taha (Elsevier, 2022)
Khat consumers might use a number of drugs for underlying conditions; however the potential drug-herb interaction between khat and other drugs including Irbesartan (IRB) is unknown. The present study was conducted to evaluate the effects of khat chewing on pharmacokinetic profile of IRB, a commonly available antihypertensive agent. The pharmacokinetic profile of orally administered IRB (15.5 mg/kg) with and without pre-administration of khat (12.4 mg/kg) were determined in Sprague-Dawley rats. IRB was estimated in rat plasma samples using a newly developed HPLC method. The chromatographic separation of the drug and internal standard (IS) was performed on a C-18 column (Raptor C-18, 100 mm × 4.6 mm id.; 5 µm) using a mobile phase consisting of 10 mM ammonium acetate buffer (pH 4.0) and acetonitrile in a ratio 60:40 v/v. Acceptable linearity for IRB was recorded at 1 - 12 µg/mL concentration range (R2 > 0.99). Intra-day and inter-day precision (%RSD = 0.44% − 3.27% and 0.39-1.98% respectively) and accuracy (% recovery = 98.3 - 104.3%) in rat plasma was within the acceptable limit according to USFDA guidelines. The AUC0-t was found to be significantly increased in IRB-khat co-administered rats as compared to rats receiving IRB only; whereas, the Tmax (0.5 h) value remained unchanged. Results of this study revealed that the IRB level considerably increased in rat plasma upon co-administration of khat. This might be due to the inhibition of CYP2D9 by khat which is the principal cytochrome P450 isoform responsible for IRB metabolism.